The Representation of Orlando Shooting in Online News Articles of Fox News and Al Jazeera: A Critical Discourse Analysis - Hengki Agus Rifa'i (Universitas Negeri Padang, 2020)
This study specifically discusses the representation of Orlando shooting, the deadliest mass shooting in the modern U.S. history taking place on June 11, 2016 in Florida, including the portrayal of the Muslim offender and the similarities and differences in contents of the shooting coverage in online news articles of two media, Fox News and Al Jazeera. Online news articles about the shooting from Fox News and Al Jazeera were selected as the data in this study. Social Actor Representation of Van Leeuwen (2008), News Schemata of Van Dijk (1986), and the analysis of socio-cultural practices of Fairclough (1995) were used to analyze data. The results of analysis showed that there were eight representational categories used by both media to portray the offender. In addition, both media provided similar coverage about the details and chronology of the shooting, the previous investigations on the offender, and comments from witnesses and the owner of the club, but differed in presenting the offender’s personal details and his association to ISIS terrorist group. Lastly, there were three socio-cultural practices – institutional context, situational context, and societal context – that explained the shooting and its different coverage in both media.